Evaluation of the quality of life of milk producers from Taquari Valley (Research, Society and Development, 2021)
Introduction: Quality of life (QoL) does not have a fully defined concept yet, however, it is possible to measure it in different ways. One of the ways to make your assessment is through the WHOQOL-bref questionnaire, which was created by the World Health Organization (WHO). Objective: Evaluate the QoL of dairy farmers in Taquari Valley. Methodology: The WHOQOL-bref questionnaire was applied to 108 dairy farmers in Taquari Valley in order to assess the domains and aspects that interfere with their QoL. After that, descriptive statistical analysis of the data obtained with the questionnaire was performed. Later, these data were compared with other studies that also used this questionnaire. Results: The analysis of these data showed that, although the overall average indicates, compared to other studies, the results obtained in Taquari Valley are better, the evaluation of each domain independently may indicate that numerous factors can be changed to improve the QoL of producers, especially in the psychological sphere. Conclusion: The application of the questionnaire was effective, considering that it was possible to observe which parameters are satisfactory – or not – with regard to the perspective of QoL of each of the participants.